2010
DOI: 10.3109/00498251003710269
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism, pharmacokinetics and excretion of the GABAAreceptor partial agonist [14C]CP-409,092 in rats

Abstract: The metabolism and excretion of a GABA(A) partial agonist developed for the treatment of anxiety, CP-409,092; 4-oxo-4,5,6,7-tetrahydro-1H-indole-3-carboxylic acid (4-methylaminomethyl-phenyl)-amide, were studied in rats following intravenous and oral administration of a single doses of [(14)C]CP-409,092. The pharmacokinetics of CP-409,092 following single intravenous and oral doses of 4 and 15 mg kg(-1), respectively, were characterized by high clearance of 169 + or - 18 ml min(-1) kg(-1), a volume of distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…These results provided strong evidence that the metabolism of (1) was mediated by MAO-A, not CYP450 or MAO-B. The formation of M6 in vitro is consistent with its formation in rats dosed 100 mg/kg of 14 C(1) (Kamel et al, 2010). MAO enzymes are present not only in liver but in several extra-hepatic tissues (Kalgutkar et al, 2001), thus the observation of MAO-A mediated metabolism of (1) in human hepatocytes and HLM likely represents only a small capacity of the total contribution of this enzyme to clearance of (1) in vivo and also likely contributes to the unanticipated low exposure.…”
Section: The Biopharmaceutics Classification System and Biopharmaceutsupporting
confidence: 85%
See 1 more Smart Citation
“…These results provided strong evidence that the metabolism of (1) was mediated by MAO-A, not CYP450 or MAO-B. The formation of M6 in vitro is consistent with its formation in rats dosed 100 mg/kg of 14 C(1) (Kamel et al, 2010). MAO enzymes are present not only in liver but in several extra-hepatic tissues (Kalgutkar et al, 2001), thus the observation of MAO-A mediated metabolism of (1) in human hepatocytes and HLM likely represents only a small capacity of the total contribution of this enzyme to clearance of (1) in vivo and also likely contributes to the unanticipated low exposure.…”
Section: The Biopharmaceutics Classification System and Biopharmaceutsupporting
confidence: 85%
“…rat (Kamel et al, 2010) suggested multiple possible clearance mechanisms of (1) including both oxidative metabolism as well as a major elimination pathway via the fecal route as unchanged 14 C(1). The pharmacokinetic profile of (1) in humans was unexpected since studies done to characterize the metabolism and disposition in animals did not offer any indication that (1) would show low oral exposure.…”
mentioning
confidence: 99%
“…Ці сполуки приваблють спеціалістів в галузі медичної хімії як міметики індолу з великою долею sp 3 -гібридизованих атомів, адже заміна плоского каркасу ациклічними фрагментами є загальною стратегією, яка сприяє оптимальному зв'язуванню з активними центрами ферментів та забезпечує кращу розчинність субстанцій [5]. Серед похідних піролоциклогексанонів відомий антипсихотичний препарат моліндон [6], агоніст ГАМК рецепторів для лікування тривожних станів [7] та потужний інгібітор теплового шоку специфічного білка при лікуванні раку [8]. Саме реакційна здатність пірольного циклу та карбонільної групи циклогексенового фрагмента зумовлюють цінність 4,5,6,7тетрагідроіндол-4-онів як потенційних будівельних блоків для синтезу важливих структур для потреб медичної хімії та спектроскопічних досліджень.…”
Section: вступunclassified
“…In the process, the amine is converted to an unstable imine intermediate, which is hydrolyzed non-enzymatically to aldehyde or ketone. Despite the commonalities, these enzymes are biochemically differentiated by their substrate and inhibitor specificities (Johnston, 1968;Murphy, 1978;Cawthon and Breakefield, 1979;Trevor et al, 1987;Waldmeier, 1987;Janssens de Varebeke et al, 1990;Nair et al, 1993;Dixon et al, 1994;Kopin, 1994;Tipton, 1994;Hauptmann et al, 1996;Youdim et al, 2001;Caccia et al, 2006;Kamel et al, 2010;Finberg and Rabey, 2016). Representative substrates and inhibitors of MAO A and B are shown in Supplementary Figure S2.…”
Section: Introductionmentioning
confidence: 99%